Violence in the Discourses of Violence - the Case of Zimbabwean Political Crisis - Saidi, Umali; Munemo, Douglas (International Journal of Asian Social Science, 2012)
Zimbabwe has undergone a vicious political showdown and violence has been topical in the analysis of the Zimbabwean political crisis. This article analyses discourses on Zimbabwe since the advent of the Zimbabwean political crisis. It reveals that the discourse used has not only exacerbated violence but has also been violent to the readers of the literature. Further, it exposes encampments in the writings on Zimbabwean politics and the polarization that exists between neo-colonial and globalization forces against pan-African and nationalist forces. This schism has unleashed a whole new perception of Zimbabwe and its identity in the global community and has determined the nature of its relations to the same. This has choked attempts by Zimbabweans to tell the Zimbabwean story as it should be in terms of its history, identity and dignity for the heritage of Zimbabwe’s future generations. This article is a product of the analysis of various discourses on Zimbabwe and advances the notion that political crisis in the country can only be realized should the violence in these discourses find peace. Through Critical Discourse Analysis we are able to pluck out the violence within the discourse and advances that political resolution to this crisis can only be realized through studies such as these.